2011
DOI: 10.1016/s1674-8301(11)60040-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of minocycline on the expression of NGF and HSP70 and its neuroprotection role following intracerebral hemorrhage in rats

Abstract: The present study was aimed to investigate the effects of minocycline (MC) on the expression of nerve growth factor (NGF) and heat shock protein 70 (HSP70) following intracerebral hemorrhage (ICH) in rats, and explore the neuroprotective function of MC. Seventy-eight male SD rats were randomly assigned to three groups: the ICH control group (n = 36), ICH intervention group (n = 36) and sham operation group (n = 6). The ICH control group and ICH intervention group were subdivided into 6 subgroups at 1, 2, 4, 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(29 reference statements)
2
4
0
Order By: Relevance
“…Previous studies indicated that NGF might be related not only to a neuroprotective activity against apoptosis, but also to the formation of new neural pathways, since NGF had the ability to promote neural plasticity and axonal regeneration [ 54 ]. In addition, previous study showed that minocycline treatment increased the number of NGF positive cells in accordance with the result of present study that was the reason of the increasing of gene expression and protein secretory [ 55 ]. The underlying mechanism might be that minocycline could regulate the expression of TrkA, which binds to NGF with high affinity and activates the downstream PI-3K/Akt pathway to inhibit the excessive release of glutamate to reduce brain injury due to Ca 2+ overload, that enhance cell survival and neuronal differentiation [ 55 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies indicated that NGF might be related not only to a neuroprotective activity against apoptosis, but also to the formation of new neural pathways, since NGF had the ability to promote neural plasticity and axonal regeneration [ 54 ]. In addition, previous study showed that minocycline treatment increased the number of NGF positive cells in accordance with the result of present study that was the reason of the increasing of gene expression and protein secretory [ 55 ]. The underlying mechanism might be that minocycline could regulate the expression of TrkA, which binds to NGF with high affinity and activates the downstream PI-3K/Akt pathway to inhibit the excessive release of glutamate to reduce brain injury due to Ca 2+ overload, that enhance cell survival and neuronal differentiation [ 55 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, previous study showed that minocycline treatment increased the number of NGF positive cells in accordance with the result of present study that was the reason of the increasing of gene expression and protein secretory [ 55 ]. The underlying mechanism might be that minocycline could regulate the expression of TrkA, which binds to NGF with high affinity and activates the downstream PI-3K/Akt pathway to inhibit the excessive release of glutamate to reduce brain injury due to Ca 2+ overload, that enhance cell survival and neuronal differentiation [ 55 ]. Glial cell-line derived neurotrophic factor (GDNF) belongs to the TGF-β family of neurotrophic factors and plays various and distinct roles in the neuronal signaling pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Power et al [36] demonstrated that post-ICH in vivo treatment with minocycline significantly reduced brain level of MMP-12, glial activation and apoptosis, and improved neurobehavioral outcomes in rats. Several experimental studies confirmed the role of minocycline administration in reducing BBB damage [84,85], inhibition of microglia activation [86], attenuation of perihematomal edema, neurological deficits, and brain atrophy [87][88][89]. In rat collagenase-induced ICH models, delayed minocycline administration significantly reduced MMP-12 levels, but it is worth to notice that its efficacy was lost and no effects on neuronal loss were observed when treatment was continued for 7 days [90].…”
Section: Inhibition Of Mmps As a Potential Therapeutic Target For Ichmentioning
confidence: 84%
“…In autologous blood induced ICH rats, administration of minocycline facilitates an "M2"-like polarization and increases microglia-derived BDNF; enhanced neurogenesis is observed with more DCX and Tuj-1 positive neuron-like cells than in a control group at 24 h after ICH onset [144]. Another study reported NGF elevation by minocycline after collagenase ICH [145]. However, minocycline injection is documented to inhibit angiogenesis by downregulating the level of VEGF and its receptors after experimental ICH, which may hinder tissue regeneration in the late phase [146].…”
Section: Strategies To Promote Neural Regeneration After Ich 61 Medicationsmentioning
confidence: 97%